Antithrombotic drugs do not increase intraoperative blood loss in emergency gastrointestinal surgery: a single-institution propensity score analysis - Matsuoka, Tadashi (World J Emerg Surg, 2019)
BACKGROUND: The use of antithrombotic drugs is increasing with the aging population. Prior to elective procedures, antithrombotic drugs are often discontinued. For emergency procedures in patients taking antithrombotic drugs, their effect cannot be attenuated which may lead to an increased risk of hemorrhagic events. However, there are few studies showing increased intraoperative blood loss in patients taking antithrombotic drugs who undergo emergency gastrointestinal surgery. The aim of this study is to determine whether the use of antithrombotic agents increases intraoperative blood loss in emergency gastrointestinal surgery. METHODS: A retrospective review of patients who underwent emergency abdominal surgery between January 2013 and December 2017 was conducted. The primary outcome measure was intraoperative blood loss. Patients were divided into the antithrombotic drug group and a control group, and a propensity score was developed using multivariate logistic regression. We use 1:1 propensity score matching analysis to compare outcomes between the two groups. RESULTS: Of 1555 patients included in this study, 1184 patients, including 170 patients taking antithrombotic drugs, were eligible for propensity score matching analysis. A 1:1 matching yielded 117 well-balanced pairs. There was no statistically significant difference in intraoperative blood loss (antithrombotic drug group vs control group, median (interquartile): 60 (225–10) vs 100 (243–10) ml, p = 0.43). CONCLUSIONS: This study suggests that antithrombotic drugs do not increase intraoperative blood loss in patients undergoing emergency gastrointestinal surgery. Emergency gastrointestinal surgery for patients currently taking antithrombotic drugs can be performed safely, and the use of antithrombotic drugs is not a reason to delay surgical intervention.